2020
DOI: 10.1016/j.diabres.2020.108437
|View full text |Cite
|
Sign up to set email alerts
|

Fasting blood glucose level is a predictor of mortality in patients with COVID-19 independent of diabetes history

Abstract: Clinical laboratory, and treatment data of inpatients with laboratory-confirmed COVID-19 were collected and analyzed. Outcomes of patients with and without pre-existing diabetes were compared. The associations of diabetes history and/or FBG levels with mortality were analyzed. Multivariate cox regression analysis on the risk factors associated with mortality in patients with COVID-19 was performed. Results: A total of 941 hospitalized patients with COVID-19 were enrolled in the study. There was a positive rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 26 publications
(32 reference statements)
4
37
1
1
Order By: Relevance
“…There were 9045 patients from 12 studies included in this systematic review and meta-analysis [ Fig. 1 ] ( Cai et al, 2020 ; Chen et al, 2021 ; Coppelli et al, 2020 ; Deng et al, 2020 ; Gastélum-Cano et al, 2021 ; Huh et al, 2020 ; Li et al, 2020 ; Liu et al, 2020 ; Sardu et al, 2020 ; Sun et al, 2020 ; Wang et al, 2020 ; Zhang et al, 2020 ). Baseline characteristics of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 9045 patients from 12 studies included in this systematic review and meta-analysis [ Fig. 1 ] ( Cai et al, 2020 ; Chen et al, 2021 ; Coppelli et al, 2020 ; Deng et al, 2020 ; Gastélum-Cano et al, 2021 ; Huh et al, 2020 ; Li et al, 2020 ; Liu et al, 2020 ; Sardu et al, 2020 ; Sun et al, 2020 ; Wang et al, 2020 ; Zhang et al, 2020 ). Baseline characteristics of the included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes, especially newly diagnosed diabetes ( Sathish et al, 2021a ), has been shown to increase mortality in patients with COVID-19 ( Huang et al, 2020a ; Shrestha et al, 2021 ) Individual studies have studied the association between fasting hyperglycemia and poor outcomes in COVID-19 patients ( Cai et al, 2020 ; Chen et al, 2021 ; Coppelli et al, 2020 ; Li et al, 2020 ; Liu et al, 2020 ; Wang et al, 2020 ); most showing a positive association, while a few have not ( Gastélum-Cano et al, 2021 ). In patients with diabetes, hyperglycemia may also represent a glycemic poor control, in addition to the acute stress caused by infection.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia on hospital admission in severely ill people with COVID-19 is very well recognized and is predictive of a poor outcome, even in subjects without pre-existing diabetes ( Cai et al., 2020 ; Fadini et al., 2020 ; Huang et al., 2020b ; Mamtani et al., 2020a ). For example, dysregulated glucose control was associated with poor outcomes in 1,122 hospitalized people with COVID-19 analyzed in the Glytec database from March 1 to April 6, 2020 ( Bode et al., 2020 ).…”
Section: Glucose Control and Covid-19 Outcomesmentioning
confidence: 99%
“…The lack of presentation of the blood glucose levels in the index study captivates attention, particularly when there is an accumulating literature on the prognostic role of the on-admission hyperglycaemia in COVID-19 regardless of the diabetic status of the diseased subset [ [2] , [3] , [4] ]. In this context, a systematic review and dose-response meta analysis by Lazarus et al (comprising of 35 studies and a total of 14,502 patients) reveal a 33% accentuation in the risk of COVID-19 disease severity for every 1 mmol/L increase in the on-admission fasting blood glucose [ 2 ].…”
mentioning
confidence: 99%